MSCs ameliorate hepatocellular apoptosis mediated by PINK1-dependent mitophagy in liver ischemia/reperfusion injury through AMPKα activation - Zheng, Jun (Cell Death Dis, 2020)
Hepatocyte apoptosis is the main pathophysiological process underlying liver ischemia/reperfusion (I/R) injury. Mitochondrial abnormalities have a vital role in hepatocellular damage. The hepatoprotective effects of mesenchymal stem cells (MSCs) have been previously demonstrated. In this study, we aim to investigate the effect and potential mechanism of MSCs against liver I/R injury. Effects of MSCs were studied in mice liver I/R injury model and in a hypoxia/reoxygenation (H/R) model of L02 hepatocytes. The potential mechanisms of MSCs on these in vivo and in vitro I/R-induced hepatocellular apoptosis models were studies. Accompanied by the improvement of hepatic damage, MSCs exhibited capabilities of controlling mitochondrial quality, shown by reduced mitochondrial reactive oxygen species (mtROS) overproduction, decreased the accumulation of mitochondrial fragmentation, restored ATP generation and upregulated mitophagy. Furthermore, we descripted a potential mechanism of MSCs on upregulating mitophagy and found that the reduced Parkin and PINK1 expression and inactivated AMPKα pathway were observed in the liver tissue in I/R model. These effects were reversed by MSCs treatment. In vitro study showed that MSC-conditioned medium (MSC-CM) suppressed hepatocellular apoptosis and inhibited mtROS accumulation in the H/R environment. And these effects of MSC-CM were partially blocked after the cells were transfected with PINK1 siRNA or added with dorsomorphin. Collectively, our findings provide a novel pharmacological mechanism that MSCs exert hepatoprotective effect in liver I/R injury via upregulating PINK1-dependent mitophagy. In addition, this effect might be attributed to the modulation of AMPKα activation.